Strategic Management in Increasing Teacher Work Motivation - Ramin Muttaqien (International Journal of Nusantara Islam, 2021)
The existence of schools is one component in supporting the goals of national education, where educational tasks can actually be categorized into "managerial" tasks which are managed by education managers assisted by education personnel in various fields of expertise. This shows that the sustainability of educational institutions cannot be separated from the applied managerial system. The application of management patterns both institutionally and with good resources will lead to an educational institution that is able to keep up with environmental changes.